The FTA Geoportal Manual for Contributors - CGIAR Research Program on Forests, Trees and Agroforestry (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
The FTA Geoportal needs the active involvement of contributors, selected individuals given the authority to add new data and metadata to the geoportal, to ensure that the portal is always operational and up to date. A back-end application has been developed, along with the geoportal, to allow contributors to access and maintain data. This application is delivered via a web-based user-interface that is designed to be as easy and as simple as possible for the contributors to use in the most effective and efficient way.